Immunomodulation in stable renal transplant recipients with concomitant tacrolimus and sirolimus therapy - Khanna, Ashwani (BioMed Central, 2002)
BACKGROUND: Long term treatment with immunosuppressive agents results in nephrotoxicity in renal transplant recipients. We explored the effect of combination of Tacrolimus (TAC) and Sirolimus (SRL) on the immune system in renal transplant recipients. METHODS: 10 stable renal transplant recipients were selected to participate in a pharmacokinetic study with a combination of TAC and SRL. Blood was drawn on day zero and 14 days post treatment. Lymphocyte proliferation was quantified by (3)H-thymidine uptake assay (results expressed as counts per minute). The mRNA expression was studied by RT-PCR and serum levels of cytokines were quantified by ELISA and a cytokine bead array system. RESULTS: Lymphocyte proliferative response to PHA (p < 0.05), Con A (p < 0.006) and Anti-CD3 (p <0.005) were significantly decreased in patients who received both TAC and SRL compared to TAC alone. The mRNA expression of proinflammatory cytokines TNF-α (p < 0.05), cyclins G (p < 0.01) and E (p < 05) were decreased, and of TGF-β (p < 0.03) and p21 (p < 0.05) were increased in patients treated with this combination. Circulating levels of IFN-γ (p < 0.04), IL-4 (p < 0.02), and Il-2 (p < 0.03) were significantly inhibited and elevation of TGF-β (p < 0.04) was observed in patients treated with TAC and SRL combination. CONCLUSION: These novel findings demonstrate that addition of SRL to TAC therapy enhances immuno modulation and causes increased immunosuppression providing a rationale for this concomitant therapy.